THE EFFECT OF MANAGERIAL ABILITY, ENVIRONMENTAL PERFORMANCE, AND BOARD OF COMMISSIONERS ON CARBON EMISSION DISCLOSURE - Padilah, Dela Nurul; Ulupui, I Gusti Ketut Agung; Zairin, Gentiga Muhammad (Neraca: Jurnal Ekonomi, Manajemen dan Akuntansi, 2025)
This study aims to provide empirical evidence on the influence of managerial ability, environmental performance, and the board of commissioners on carbon emissions disclosure. The sampling technique used is purposive sampling. The secondary data utilized were obtained from annual reports and sustainability reports available on www.idx.com, the official websites of companies meeting the sample criteria, as well as from Refinitiv Eikon and the website of KLHK Indonesia. The analysis technique applied is multiple linear regression with panel data, using the EViews 12 software. The results of the study indicate that: (a) managerial ability has no effect on carbon emissions disclosure; (b) environmental performance has a positive effect on carbon emissions disclosure; and (c) the board of commissioners has a positive effect on carbon emissions disclosure.